Étudier les motifs vestimentaires en Grèce Ancienne. Méthodologie et enjeux - Quentin Richard (Les Cahiers de l'École du Louvre)
Because of the Greek climate, few textile fibres of animal or vegetable origin have survived. The absence of significant archaeological evidence makes it difficult to study the appearance of ancient clothing. The production of terracotta figurines provides numerous iconographic testimonies of clothing ornaments, which should be classified to provide a maximum of information. The corpus makes it possible to illustrate the richness of the adornment present on clothing and to follow the evolution of its use thanks to objective data. It also provides a better understanding of archaeological textiles, currently very fragmentary. This article presents the methodology adopted for research and the issues that guided it.